A CFD INVESTIGATION INTO MOLTEN METAL FLOW AND ITS SOLIDIFICATION UNDER GRAVITY SAND MOULDING IN PLUMBING COMPONENTS - Sirawit Namchanthra (2022)
Metal casting using the solidification of molten metal flows involves complex heat transference during production. This can cause defects in the workpiece, affecting the efficiency of production. This research will use the Computational Fluid Dynamics (CFD) technique to investigate the filling, solidification, and cooling stages of the production of a component for plumbing. The CFD program FLOW 3D CAST v5.03 tracked the leading edge of the molten metal liquid (based on the Volume of Fluid (VOF) method). A two-equation k–ɛ turbulence was adopted to provide a Reynold term, and it should be noted that the geometry of the molten liquid and the internal chamber is the same as in the actual production line. The simulation shows how different pouring temperatures affect the runner, and that the pouring temperature influenced the behavior of the molten metal flow, resulting in defects on the workpiece. Moreover, the runner and its number affected the liquid metal flow and affected the defect's location during the solidification period. Future work will verify the results between the simulation and experiments, and further investigate possible defect locations on the surface of the workpiece, which could be a critical criterion in further discussions.